2023
DOI: 10.3389/fcvm.2023.1198020
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin deposition on bovine pericardium tissue used for bioprosthetic heart valve drives its calcification

Bastien Poitier,
Jeanne Rancic,
Ulysse Richez
et al.

Abstract: BackgroundBioprosthetic heart valves (BHVs) are less thrombogenic than mechanical prostheses; however, BHV thrombosis has been proposed as a risk factor for premature BHV degeneration.ObjectivesWe aimed to explore whether fibrin deposition on bovine pericardium tissue could lead to calcification.MethodFibrin clot was obtained by blending three reagents, namely, CRYOcheck™ Pooled Normal Plasma (4/6), tissue factor + phospholipids (Thrombinoscope BV), and 100 mM calcium (1/6), and deposited on pericardium discs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…We recently demonstrated heightened calcification due to fibrin deposition on bovine pericardium tissue in a rat model. 4 The GALILEO trial reported a diminished SLT incidence in patients treated with rivaroxaban versus those undergoing antiplatelet therapy post-transcatheter aortic valve replacement but elevated rates of mortality and bleeding complications. 5 Importantly, participants in the GALILEO trial were older than our patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated heightened calcification due to fibrin deposition on bovine pericardium tissue in a rat model. 4 The GALILEO trial reported a diminished SLT incidence in patients treated with rivaroxaban versus those undergoing antiplatelet therapy post-transcatheter aortic valve replacement but elevated rates of mortality and bleeding complications. 5 Importantly, participants in the GALILEO trial were older than our patient cohort.…”
Section: Discussionmentioning
confidence: 99%